Photoshop elements 11 all-in-one for dummies - Obermeier, Barbara (John Wiley & Sons, 2013)
Photoshop Elements is the top selling consumer photo editing software and Adobe continues to add innovative features that allow digital photo enthusiasts to do it all. This value-packed reference combines nine content-rich minibooks in one complete package. User-friendly and detailed, it covers the key features and tools that beginner and experienced users need to create high-quality images for print, e-mail, and the web using the latest release of Photoshop Elements: Photoshop Elements 11. Presented in full color, this resource goes beyond the basics of the application and is undoubtedly the most comprehensive Elements book on the market.